Differential determinants of virulence in two Mycobacterium tuberculosis Colombian clinical isolates of the LAM09 family (2019)
ABSTRACT: The heterogeneity of the clinical outcome of Mycobacterium tuberculosis (Mtb) infection may be due in part to different strategies used by circulating strains to cause disease. This heterogeneity is one of the main limitations to eradicate tuberculosis disease. In this study, we have compared the transcriptional response of two closely related Colombian clinical isolates (UT127 and UT205) of the LAM family under two axenic media conditions. These clinical isolates are phenotypically different at the level of cell death, cytokine production, growth kinetics upon in vitro infection of human tissue macrophages, and membrane vesicle secretion upon culture in synthetic medium. Using RNA-seq, we have identified different pathways that account for two different strategies to cope with the stressful condition of a carbon-poor media such as Sauton's. We showed that the clinical isolate UT205 focus mainly in the activation of virulence systems such as the ESX-1, synthesis of diacyl-trehalose, polyacyl-trehalose, and sulfolipids, while UT127 concentrates its efforts mainly in the survival mode by the activation of the DNA replication, cell division, and lipid biosynthesis. This is an example of two Mtb isolates that belong to the same family and lineage, and even though they have a very similar genome, its transcriptional regulation showed important differences. This results in summary highlight the necessity to reach a better understanding of the heterogeneity in the behavior of these circulating Mtb strains which may help us to design better treatments and vaccines and to identify new targets for drugs.